Comics as a Physical Education Tool for Health Promotion in Brazilian Primary Education, Based on Paulo Freire's Principles of Empowerment - George Bernard Soares Nascimento; Marcelo de Maio Nascimento; Luciana Márcia Gomes de Araújo; Élvio R. Gouveia; Andreas Ihle (MDPI AG, 2023)
Incorrect postural habits developed already at an early age are predictors of low back pain and functional limitations in adult life. Postural education programs (PEPs) are activities developed in Physical Education classes with the aim of promoting healthy habits. One tool used by PEPs is comics. The objective of this study was to develop comics and apply them as a teaching tool in PEPs for students aged seven to ten years. The procedures were based on individual empowerment principles, including creation activities, reading, painting, crosswords, and discussion of comics. The activities strengthened the students' interactions, gaining new knowledge that required cognitive and expressive resources to interpret, associate, and conceptualize themes of correct body posture. During six weeks of intervention, knowledge about body posture, anatomy, and health promotion exercises increased significantly in relation to the beginning of activities. The comic book proved to be an effective, attractive, and low-cost didactic resource.